Growth of big-leaf mahogany (Swietenia macrophylla King) in natural forests in Belize - Shono, K.; Snook, Laura K. (2004)
Four years of annual diameter measurements of 75 big-leaf mahogany (Swietenia macrophylla King) trees in natural forests in northwestern Belize were analyzed to determine growth rates. Mean diameter increment among the sample trees exceeded 1 cm y-1, with slightly higher growth rates among trees > 50 cm dbh. Inter-individual variation in growth rates was significant, with the fastest-growing individuals growing at rates greater than 2 cm y-1. Inter-annual variation in growth rates was also significant, and diameter growth of 1.21 ±± 0.1 cm during a wetter year (1456 mm ppt) exceeded by 75% diameter growth of 0.69 ±± 0.1 cm during a drier year (1181 mm ppt). The growth of these sample trees reveals that mahogany trees as small as 23 cm dbh that are left standing after harvests can be expected to attain the commercial diameter of 60 cm during the 40 years between cutting cycles.